Combined Use of Intraperitoneal and Incisional Bupivacaine Reduces Pain Severity after Diagnostic Laparoscopic in Infertile Women (Journal of Shaheed Suhrawardy Medical College, 2019)
Introduction: Diagnostic laparoscopy offers an excellent means through direct visualization to elucidate the hidden pathology in the absence of clinical signs and symptoms suggestive of a cause of infertility. But postoperative pain management remains a major challenge after laparoscopic surgeries. Approximately one half of all surgical procedures, postoperative pain is inadequately treated.Aim: A randomized, double-blind, placebo-controlled trial was conducted with an objective to evaluate the post-operative analgesic efficacy of intraperitoneal and incitional bupivacaine infiltration at the end of diagnostic laparoscopy in infertile womenMethods: 40 infertile women, enrolled for diagnostic laparoscopy were divided randomly into two groups. Group A received intraperitoneal bupivacaine (0.25%) 10 ml and incisional infiltration of NS 10 ml, Group B received intraperitoneal bupivacaine 10 ml and incisional infiltration of bupivacain 10 ml. In postoperative period, Visual Analogue Score (VAS) was recorded up to 24 hours. Postoperative analgesic requirements, and side effects were recorded.Results: The Visual Analogue Score (VAS) during the first postoperative 24 hours was significantly lower in group B compared to group A. Time to first analgesia required was delayed and total analgesic consumption was lower in group B which was statistically significant.Conclusions: It is concluded that combined intraperitoneal instillation and incision site infiltration of bupivacaine in diagnostic laparoscopy may significantly reduce the postoperative pain and analgesic requirement.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 69-72